Impacts of congestion in the city of Batna, Algeria - GUEHTAR, Naziha; SAIDI, Asma (2008)
The improvement of the living conditions requires that an increasing attention be given to the fight against the various nuisances effects which characterize the use of the motor vehicles: the Network congestion, the road insecurity, air pollution, noise, etc... In this article we will present a study on places affected by the congestion in the city of Batna. The results obtained enabled us to formulate a set of recommendations relating to the organization and the management of transport.